Determining the contribution of the national school nutrition programme to the total nutrient intake of Mogale city learners - Monala, Pumla Kgomotso (Vaal University of Technology, 2018)
The purpose of this study was to determine the contribution of the National School Nutrition Programme (NSNP) has made on the total nutrient intake of Kagiso learners. This was done by investigating the nutrient intake of school children participating in the NSNP (experimental group) and comparing this to the nutrient intake of learners participating in the tuck-shop or lunch box (control group) from one school. The research methodology was undertaken in two phases, namely phase one; planning and phase two; data collection and analysis. The following measuring methods were applied; socio-demographics, household food insecurity assessment scale, anthropometry measurements, food frequency questionnaires (FFQ), 24-hour recall and the observation of the NSNP during the school lunch breaks. Anthropometry measurements were analysed according to the World Health Organization standards (WHO 2008), socio-demographics, and household food insecurity assessment scale and FFQ were captured on an Excel spreadsheet by the researcher and analysed using the Statistical Package for Social Sciences (SPSS) version 22.0 for descriptive statistics such as frequencies, standard deviations and confidence intervals. An expediency sample of 160 primary school children aged 6-13 years, including girls (n=84) and boys (n=76) and 106 caregivers were recruited into the study. The results showed that majority of caregivers (59%) completed secondary level education, followed by 39% with primary level or college completion (2%). The employment rate in the Kagiso households of the sampled group was low with 20% of caregivers being unemployed. Out of the 76% of the employed caregivers, 26% were permanently employed and 51% were temporarily employed with contract work and piece jobs. The highest monthly income (42%) was between R1000-R3000 and the lowest (38%) was less than R1000 with only R101-R200 to spend on food per week. The food insecurity status of Kagiso learners showed that 44% of school children were food secure, and 56% were food insecure – of these, 29% experienced hunger. Heightfor-age, weight-for-age and BMI-for-age were measured for all of the 160 children. The group was categorized as follows; school children participating in the NSNP (n=59) and children using the tuck-shop foods (n=35) and lunch box (n=66). The nutritional status of Kagiso learners from the sampled group showed that more boys were stunted (13%) and wasted (12%) while of the girls, 30% were at risk of being overweight, with only 2% reported to be overweight. The majority of boys reported to be stunted and wasted were from the NSNP group and the girls reported to be overweight or at risk of being overweight were from the tuck-shop group. Thus, the learners from the lunchbox had optimum growth status when compared to the other two groups. The respondents consumed a mainly high carbohydrate diet with a low consumption of vegetable and fruits. The results from the Food Variety Score (FVS) revealed a low individual mean (2.25±1.57) in the legume and nuts group, followed by a medium individual mean (7.9±2.81) in the fruits and other juices group, 7.16±2.68 in the vegetable group, and lastly, the highest individual mean (9.26±3.04) in the cereal, roots and tubers diversity. The results from the top 20 popular food items ranked as follows; maize meal stiff (1st), maize meal porridge (5th), white rice (6th), white bread (7th) brown bread (9th), potato fries (12th), breakfast cereal (13th) and samp and beans (14th). Cabbage (15th) and pumpkin (20th) were the most popular vegetables and there were no fruits within the top 20 popular list of food items. The Nutrient Adequacy Ratio (NAR) of the NSNP (n=59) meals was below the 1/3 (33.3%) and 30% dietary requirements for lunch meals. This was very evident regarding vitamin A (16.85%), energy kilojoules (23.78%), calcium (18%), folate (26.72%), zinc (15.71%), dietary fiber (25.71%) and iodine (4.65%). Iron (38.98%) was slightly above the 1/3 and 30% dietary intake, but there were a high percentage (61%) of respondents who did not meet the EARs of 5.9mg for iron. The results revealed an inadequate contribution by the NSNP to the nutrient intake of Kagiso learners. The poor intake of folate, vitamin A and dietary fiber in this sampled group is linked to the low consumption of vegetable and fruits. Results from this observational study showed that a majority of respondents do not participate in the NSNP when they do not have their own eating utensils. Respondents also revealed that the NSNP meals caused allergies such as skin rash while some mentioned diarrhea as the cause of not eating meals from the NSNP. Hence, a larger percentage (41%) of school children preferred to participate in the lunch box rather than in the NSNP (37%). The high prevalence of inadequate nutrient intake and the poor nutritional status of Kagiso learners in the sampled group, is an indication that strict monitoring of dietary measures needs to be implemented and continuously evaluated to ensure that positive nutritional results are obtained by the NSNP across South Africa
M. Tech. (Department of Hospitality, Tourism and PR Management, Faculty of Human Sciences), Vaal University of Technology
Keywords: school children, NSNP, nutritional status, dietary intake; Dissertations, Academic -- South Africa; Expanded Food and Nutrition Education Program; Nutrition -- Study and teaching (Primary) -- South Africa